2014
DOI: 10.1007/s12603-014-0015-5
|View full text |Cite
|
Sign up to set email alerts
|

Novel metabolic roles of L-arginine in body energy metabolism and possible clinical applications

Abstract: Although the body can synthesize L-arginine, exogenous supplementation may be sometimes necessary, especially in particular conditions which results in depleted endogenous source. Among diseases and states when exogenous supplementation may be necessary are: burns, severe wounds, infections, insufficient circulation, intensive physical activity or sterility. In recent time, the attention was paid to the use of L-arginine supplementation by athletes during intensive sport activity, to enhance tissue growth and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 62 publications
0
28
0
1
Order By: Relevance
“…31 The functions of Arg has revealed that it is in involved in the regulation of immune cells in cancer, inflammation, infections, etc. 26,[32][33][34][35][36][37][38][39][40] Arg is synthesized from glutamine, glutamate, and proline via the intestinal-renal axis in humans and other mammals (such as pigs, sheep, and rats). 32 Although the body can synthesize Arg, its supplementation may be necessary, particular in conditions which results in depleted endogenous source.…”
Section: Windmueller and Spaeth Reported That The Small Intestimentioning
confidence: 99%
See 2 more Smart Citations
“…31 The functions of Arg has revealed that it is in involved in the regulation of immune cells in cancer, inflammation, infections, etc. 26,[32][33][34][35][36][37][38][39][40] Arg is synthesized from glutamine, glutamate, and proline via the intestinal-renal axis in humans and other mammals (such as pigs, sheep, and rats). 32 Although the body can synthesize Arg, its supplementation may be necessary, particular in conditions which results in depleted endogenous source.…”
Section: Windmueller and Spaeth Reported That The Small Intestimentioning
confidence: 99%
“…In addition, it has been reported to reduce the pathogenicity of herpes simplex and influenza viruses, probably due to compromised function of proteins in the envelope . The functions of Arg has revealed that it is in involved in the regulation of immune cells in cancer, inflammation, infections, etc …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The central role of AMPK in regulating cellular ATP regeneration, makes this enzyme as a central control point in energy homeostasis. Hirstina K., and his colleagues reported that the effects of L-arginine supplementation on energy expenditure were successful independently of age or previous disease, in young sport active, elderly, older population and patients with angina pectoris [29] . Mariotti F., and his colleagues investigated the kinetics and dosdependency of dietary arginine utilization for NO compared with urea synthesis and studied the characteristics of the arginine-NO metabolic system in healthy humans.…”
Section: E F F E C T O F a L O E V E R A G E L A N D L -A R G I N I Nmentioning
confidence: 99%
“…Ketoacids have been utilized in remedying renal dysfunction, muscle fatigue, heart defects and burns (58,59,60). In a more recent example, L-arginine's positive effects on supplementation of energy expenditure regardless of age, previous incidence of diseases or activity shows promise as a metabolite therapy (61). The ketoacids like αKG and ornithine alpha-ketoglutarate, a precursor of amino acids such as glutamine, arginine and proline have shown to be effective modulators of muscle protein metabolism.…”
Section: A Metabolite-based Therapy For Admentioning
confidence: 99%